Model Hubungan Kapasitas Rekatan Balok Beton Bertulang yang Diperkuat GFRP-S terhadap Lama Perendaman Air Laut - Sultan, Mufti Amir; Djamluddin, Rudy (Department of Civil Engineering, Diponegoro University, 2019)
The construction of structures with reinforced concrete materials in coastal environments will face constraints in the form of chloride influences which can lead to a decrease in strength and even damage. One of the most popular reinforcement methods today is using a corrosion resistant Glass Fiber Reinforced Polymer (GFRP) material. This study was conducted to investigate the behavior of GFRP-S rectifying capacity in reinforced concrete beam reinforcement in 1, 3, 6, and 12 months. The test specimens consist of 10 reinforced beams with dimensions (15x20x330) cm that has been reinforced with GFRP-S in the bending area. Beams without immersion symbolized B0, immersion 1, 3, 6, and 12 months each given symbols B1, B3, B6 and B12. The test specimen is loaded statically until it fails. To record the data when testing is installed strain gauge and LVDT. From the result of the research, it can be seen that there is a decrease of GFRP-S rectification capacity in the test specimen after soaking in seawater. The value of the decrease in the capacity of the bonding can be predicted by using the equation